Prevalence of diabetes in pregnancy and microvascular complications in native Indonesian women: The Jogjakarta diabetic retinopathy initiatives in pregnancy (Jog-DRIP) - Widyaputri, Felicia (Public Library of Science, 2022)
Objectives: To report the prevalence of total diabetes in pregnancy (TDP) and diabetes-related microvascular complications among Indonesian pregnant women. Methods: We conducted a community-based cross-sectional study with multi-stage, cluster random sampling to select the participating community health centers (CHC) in Jogjakarta, Indonesia between July 2018-November 2019. All pregnant women in any trimester of pregnancy within the designated CHC catchment area were recruited. Capillary fasting blood glucose (FBG) and blood glucose (BG) at 1-hour (1-h), and 2-hour (2-h) post oral glucose tolerance test (OGTT) were measured. TDP was defined as the presence of pre-existing diabetes or diabetes in pregnancy (FBG ≥7.0 mmol/L, or 2-h OGTT ≥11.1 mmol/L, or random BG ≥11.1 mmol/L with diabetes symptoms). Disc and macula-centered retinal photographs were captured to assess diabetic retinopathy (DR). Blood pressure, HbA1c and serum creatinine levels were also measured. Results: A total of 631/664 (95%) eligible pregnant women were included. The median age was 29 (IQR 26–34) years. The prevalence of TDP was 1.1% (95%CI 0.5, 2.3). It was more common in women with chronic hypertension (p = 0.028) and a family history of diabetes (p = 0.015). Among the TDP group, 71% had a high HbA1c, but no DR nor nephropathy were observed. Conclusions: Although a very low prevalence of TDP and no diabetes-related microvascular complications were documented in this population, there is still a need for a screening program for diabetes in pregnancy. Once diabetes has been identified, appropriate management can then be provided to prevent adverse outcomes.